2019
DOI: 10.3390/ani9060372
|View full text |Cite
|
Sign up to set email alerts
|

Food Preferences in Cats: Effect of Dietary Composition and Intrinsic Variables on Diet Selection

Abstract: A ten-year database of food preference tests (n = 1021; period 2007−2017) was used to explore the feeding behavior of domestic cats. Principal component (PC) analysis and linear regression between food nutrients and preferences (for the most preferred diet of each test; Diet A) were performed. Intake and preference for Diet A were analyzed by intrinsic cats’ variables and climate season. The PC1 (calcium (Ca), phosphorus (P), and ash), PC2 (lipids and ether extract) and PC4 (crude fiber; CF) had borderline sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Serisier and colleagues [ 64 ] found that cats consume less in winter, possibly due to negative effects on exercise levels. Conversely, Alegría-Morán and colleagues [ 51 ] found that feline food intake increased, especially in females, in winter. Similarly, both dogs and poultry were found to have increased food intake during winter, probably due to decreased calorific need to maintain body temperature [ 65 – 67 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serisier and colleagues [ 64 ] found that cats consume less in winter, possibly due to negative effects on exercise levels. Conversely, Alegría-Morán and colleagues [ 51 ] found that feline food intake increased, especially in females, in winter. Similarly, both dogs and poultry were found to have increased food intake during winter, probably due to decreased calorific need to maintain body temperature [ 65 – 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alegría-Morán and colleagues [ 50 , 51 ] analysed 1,771 preference tests conducted on 34 kennelled dogs, and 1,021 preference tests on 24 kennelled cats. They found that food preferences in both species were negatively correlated with crude fibre and dry matter levels.…”
Section: Introductionmentioning
confidence: 99%
“…Palatants incorporate many different macro- and micromolecules including proteins, amino acids, carbohydrates, fatty acids, peptides, vitamins, and minerals [ 96 ]. The aim of these ingredients is to enhance the sensory experience of the animal, particularly the umami T1R1 and T1R3 taste receptors, as cats are known to have a strong affinity for umami compounds [ 50 , 97 ]. In the pet food industry, animal protein hydrolysates have been used to create palatability enhancers via the Maillard reaction [ 98 ].…”
Section: Palatability and Preferencementioning
confidence: 99%
“…Several factors play an important role in diet selection for cats. Cats use both smell and taste in the detection and selection of foods [ 23 , 97 , 107 ]. While not as developed as in dogs, the olfactory senses are used by cats to recognise both novel and untrusted aromas [ 6 ].…”
Section: Palatability Driversmentioning
confidence: 99%
“…The mistakes that are often found in keeping pet cats include diet portion or nutritional content that is not in accordance with cats' needs, which can interfere with cats' health and cause diseases such as obesity, diabetes, colic, and nutritional imbalance [1]. Understanding the relationship between food composition and several intrinsic variables of cat dietary preferences will be useful in improving the formulation of pet diets, allowing to meet the physiological and hedonic needs of domestic cats [2].…”
Section: Introductionmentioning
confidence: 99%